Study relationship between increase of Anti-cardiolipin antibodies and Cytomegalovirus infection in pregnant women in Baghdad - Hashim Abid Abass; Ali Abdul_hussein Mahdi; Nihad Abdul_hussein Jaffer (Journal of Madenat Alelem University College, 2016)
In this study, two hundred samples of blood were taken from pregnant women which suffering from cytomegalovirus (CMV) infection in Baghdad. Diagnosis of anti-cardiolipin & CMV was done by using enzyme linked immune sorbent assay (ELISA) technique, the age of subjects were ranged from 25 to 45 years. The results were compared with control group which constitute of fifty healthy pregnant women, their age ranged from 25 to 45 years. It was observed that there is a positive correlation coefficient between anti-cardiolipin & anti-CMV titer. Also there is significant difference between mean of anti-cardiolipin and anti-CMV titers of study and control groups. It was concluded that anti-cardiolipin antibody IgM may be associated with first trimester recurrent abortions for women infected with CMV.